Relationship between Organic-C and Available-P Due to Tidal Fluctuation in South Kalimantan - Fadly Hairannoor Yusran (UNIVERSITY OF LAMPUNG, 2012)
Tidal fluctuation creates different soil chemical properties which is totally deviate from normal circumstances. Organic matter decomposition occurs with limited O2 supply, hence disturbing Carbon cycle which has a central role in the process and nutrient mineralisation. The research aimed was to describe the relationship between organic-C and available-P due to tidal fluctuation in South Kalimantan. Ten undisturbed composite samples were collected in top-soil and sub-soil. Results showed that there was no direct effect from organic-C in P availability as in other mineral soils. However, there was an indication that the relationship was influenced by maturing process of the soil. In other words, the relationship between organic-C and available-P was typical for every type of swampland and was not related to the tidal fluctuationKeywords: Available-P, organic-C, P-transformation, tidal water fluctuation [How to Cite: Yusran FH. 2012. Relationship between Organic-C and Available-P Due to Tidal Fluctuation in South Kalimantan. J Trop Soils 17 (3) : 253-257. doi: 10.5400/jts.2012.17.3.253] [Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.253]